Effects of Different Types of Exercise Training on the Cortisol Awakening Response in Children - Wegner, Mirko; Koutsandréou, Flora; Müller-Alcazar, Anett; Lautenbach, Franziska; Budde, Henning (Frontiers in Endocrinology, 2019)
Context: Due to great variability of stress-related systems, research has to produce more detailed findings to make a more meaningful statement regarding the effect of exercise training (ET) on the cortisol awakening response (CAR), especially in children. Objective: The aim of the study was to investigate the effects of different ET interventions on the CAR in children. Design and Setting: We conducted a longitudinal study for ten weeks in primary schools in Westphalia, Germany. Participants: 71 children (9-10 years old) were randomly assigned to a cardiovascular exercise group (n = 27), a motor exercise group (n = 23), or a control group (n = 21). Intervention: An experienced instructor trained the children in an after-school setting in 45 min sessions, three times a week over the course of ten weeks. Main Outcome measure: CAR was assessed on two consecutive schooldays before and after the intervention. A Shuttle Run Test was performed to determine the cardiovascular fitness. Motor fitness was assessed using the Heidelberg Gross Motor Test. Results: Children who enhanced their cardiovascular fitness over the course of the intervention showed an increased CAR after the intervention time (B = 0.213), whereas children who underwent a motor exercise intervention and at the same time gained in motor fitness exhibited a decreased CAR after intervention (B = -0.188). Conclusions: It has been speculated that other pathways are activated by different exercise interventions. The extent to which these ET effects on CAR can be applied in clinical settings needs further investigation.